Security and privacy in next-generation mobile payment systems - Zamrud, Ani Afiqah; Mansor, Hafizah (KICT Publishing, 2024)
As the number of mobile payment transactions increases, there is also an increase in crimes related to mobile payment systems. Fraud, scams, data theft, and stealing are among some crimes affecting mobile payment application users. This paper compares the features of five existing mobile payment applications in Malaysia, Boost, Grab Pay, Touch ‘n Go, MAE, and ShopeePay, to gain insights into how Malaysia’s mobile payment applications work. Besides that, this paper identifies the major security and privacy issues in mobile payment systems by assessing threats, vulnerabilities, and risks. Moreover, this paper identifies the security mechanisms of mobile payment systems. In addition, this paper discovers some methods to improve the security of mobile payment systems by conducting a literature review on the existing security properties of mobile payment systems. Hence, it is believed that a better secure mobile payment system can be developed. It would increase the trustworthiness of the users and encourage them to keep using mobile payment applications.